Problem-Based Learning Video on Ecosystem Harmony for Social Science Subject (IPAS) in Grade 5 Elementary School Students - Kadek Emy Dhyana Putri; Anak Agung Gede Agung; Anak Agung Ayu Dewi Sutyaningsih (Universitas Pendidikan Ganesha, 2025)
The students' poor learning outcomes can be attributed to the application of conventional teaching methods limited interactive media, and a lack of student engagement. This research was focused on fifth-grade elementary school students to develop problem-based learning video media for the topic